LEARNING STRATEGIES USED BY EFL STUDENTS IN LEARNING ENGLISH VOCABULARY AT MAMBAUL ULUM ISLAMIC SENIOR HIGH SCHOOL - LAILA, ALFIN NURUL HIDAYAH; WANDA DWI LESTARI; ULFA YULIASARI (Prosiding SNasPPM, 2022)
Vocabulary is one of the language aspects that must be learned by the foreign language learners. Vocabulary knowledge is often viewed as a critical tool for foreign language learners because limited vocabulary in learning a foreign language make the student’s barrier in communication. Students will find difficulties in learning English if they do not know strategies in learning vocabulary. The data collecting techniques were questionnaire. The questionnaire were distributed to 30 students at Senior High School Mambaul Ulum Islamic grade XI. The objective of this research was to know the most learning strategy mostly used by the students of vocabulary. The result of the data showed that many students employed more than one strategies in learning vocabulary. Those strategies were using metacognitive strategies, cognitive, memory and activation strategies. The most dominant strategy was repetition in memory strategy. In this strategy, most of learners believed that repetition was the best way to remember words.